Moderating role of Gender and Family Income on Green Entrepreneurial Intention factors: An empirical study on Higher Education Students (IITM Journal of Business Studies, 2024)
As the world becomes green, it emphasizes  the importance of adopting a sustainable,  environmentally and socially beneficial lifestyle.  A growing body of academic research on “going  green” offers a new standpoint on the concept of  Green Entrepreneurship. Green entrepreneurship  aims to follow classic entrepreneurial ideals while  providing additional benefits to society and the  environment at the same time. The study explores  the influence of factors, namely, entrepreneurial  creativity, university green entrepreneurial  support, green recognition, and green value  variables, on green entrepreneurial intentions,  along with the moderating role of gender, family  income and family occupation among students. Data from 600 Undergraduate and Postgraduate  students was collected using the survey method.  For this purpose, a structured questionnaire  with a five-point Likert scale was used. The  statistical techniques applied to the dataset  were confirmatory factor analysis and structural  equation modeling using SPSS, AMOS, and  process-Macro. The results revealed that all the study variables  positively and significantly influence students’  green entrepreneurial intention. Moreover,  demographic factors also influence this  relationship. Most of the previously conducted research  focuses on entrepreneurship in context  with its contribution to economic growth,  development of the economy, employment  generation, and reduction in a disparity of  income. However, less research highlighted  the green aspect of entrepreneurship and  its contribution to sustainability. Moreover,  there is a shortage of studies conducted to  understand students’ perspectives on green  entrepreneurship. The present study has  attempted to realize determinants that influence  green entrepreneurial intentions among UG and  PG students. The study’s findings will provide  directions to policymakers, entrepreneurs,  students, Educational Institutions, and  society to understand the ecosystem of green  entrepreneurship.
Keywords: Green entrepreneurship; Environmental Values; University green entrepreneurial support; Higher education, Green Value; Green recognition